Particle Collection in Imhoff Sedimentation Cones Enriches Both Motile Chemotactic and Particle-Attached Bacteria - Heins, Anneke; Reintjes, Greta; Amann, Rudolf I.; Harder, Jens (Frontiers in Microbiology, 2021)
Marine heterotrophic microorganisms remineralize about half of the annual primary production, with the microbiomes on and around algae and particles having a major contribution. These microbiomes specifically include free-living chemotactic and particle-attached bacteria, which are often difficult to analyze individually, as the standard method of size-selective filtration only gives access to particle-attached bacteria. In this study, we demonstrated that particle collection in Imhoff sedimentation cones enriches microbiomes that included free-living chemotactic bacteria and were distinct from particle microbiomes obtained by filtration or centrifugation. Coastal seawater was collected during North Sea phytoplankton spring blooms, and the microbiomes were investigated using 16S rRNA amplicon sequencing and fluorescence microscopy. Enrichment factors of individual operational taxonomic units (OTUs) were calculated for comparison of fractionated communities after separation with unfractionated seawater communities. Filtration resulted in a loss of cells and yielded particle fractions including bacterial aggregates, filaments, and large cells. Centrifugation had the lowest separation capacity. Particles with a sinking rate of >2.4 m day–1 were collected in sedimentation cones as a bottom fraction and enriched in free-living chemotactic bacteria, i.e., Sulfitobacter, Pseudoalteromonas, and Vibrio. Subfractions of these bottom fractions, obtained by centrifugation, showed enrichment of either free-living or particle-attached bacteria. We identified five distinct enrichment patterns across all separation techniques: mechano-sensitive and mechano-stable free-living bacteria and three groups of particle-attached bacteria. Simultaneous enrichment of particle-attached and chemotactic free-living bacteria in Imhoff sedimentation cones is a novel experimental access to these groups providing more insights into the diversity, structure, and function of particle-associated microbiomes, including members of the phycosphere.